Perlindungan Hukum Hak Cipta terhadap Buku Elektronik (E-Book) di Era Globalisasi - Vina Maharani; Anthon Fathanudien (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2023)
This study aims to find out the arrangements regarding electronic books (e-books) Intellectual Property for electronic books (E-books) as an aspect of Copyright associated with the Copyright Law and find out legal remedies in resolving disputes in the event of copyright infringement electronic book (E-book). This study uses a normative legal research method by concentrating on the object of study on UUHC. The results of the study show that the elucidation of Article 40 Paragraph (1) letter n of the UUHC implicitly acknowledges that the electronic book (E-book) is one of the protected adaptation creations. Therefore electronic books (E-books) are a form of adaptation or transformation of printed books so that electronic books (E-books) must be protected. For others who wish to convert a printed book into an electronic book (E-book), they must obtain permission from the creator through a license agreement made by the parties and must fulfill the legal requirements of the agreement as stipulated in Article 1320 of the Civil Code. If there is a copyright infringement in the duplication of an electronic book without the permission of the Author, then based on Article 95 Paragraph (1) UUHC the case can be resolved through a court and without going through a court. Settlement of disputes without going through a court can be done by means of arbitration, mediation, negotiation and conciliation. Specifically for court proceedings, only the Commercial Court has the authority to resolve cases in the field of copyright.